A program of telementoring in laparoscopic bariatric surgery. Issue 1 (2nd January 2016) - Fuertes-Guiró, Fernando; Vitali-Erion, Enrique; Rodriguez-Franco, Amalia
Abstract: Background This study proposes a system for teaching and surgical support with the benefits of online Information and Communications Technology (ITC) -based telementoring for laparoscopic bariatric surgery (LBS).Material and methods A system of telementoring was established between a university center and two community hospitals. Telementoring was performed via internet protocol using a direct point-to-point connection, ASDL 1.2 Mbps, time delay 150 ms, 256-bit advanced encryption standard (AES). In the period of time selected, all interventions for LBS in both hospitals were included. When patients agree with telementoring, data outcomes (operating time, hospital stay, conversion to open surgery and complications) were collected. The rest of these interventions were recorded.Results Thirty-six patients underwent elective LBS, 20 of whom were referred and accepted for telementoring. Patients selected without telementoring took longer: 200 (46) min vs 139 (33) min, p  < 0.01. There were two conversions in non-mentored groups. The hospital stay was 4.6 (0.5) days for telementored interventions and 6.7 (0.5) days without mentoring ( p  < 0.01). Four patients (12, 5%) in non-mentored groups suffered minor complications.Conclusions This program supports the safety and feasibility of telementoring in LBS. Telementoring is an alternative in community hospitals because it can improve the quality of advanced procedures of laparoscopic surgery.